Daži trīssakarīgi grafi un to saimes bez Hamiltona cikliem - Grinbergs, Emanuels (My University, 2013)
These manuscripts (in Latvian) contain examples of graphs without Hamiltonian cycles. See the flower snark J5 on the page 13. The date here 1.6.78.
Some threeconnected graphs and their families without Hamiltonian cycles
Keywords: combinatorics, graph theory, flower snarks; Rokraksts